South Africa's diplomatic recognition of the people's republic of China: building consensus amongst dissension - Hurst, Claire (My University, 2018)
The following research report is an analysis of the diplomatic history paradigm of South Africa’s switch in diplomatic recognition from the Republic of China to the People’s Republic of China in November 1996. Previously classified documentation from the Department of International Relations and Cooperation, and the African National Congress’ Liberation Archives at Fort Hare University, and with interviews with former ANC/National Executive Committee members and Department of Foreign Affairs officials, along with the inclusion of the memoirs of the former ROC and PRC ambassadors at the time of the switch, provide valuable insight into the timing of the announcement and the factors that prompted the decision. This research aims to aid our understanding of the foreign policy decision making process under the Mandela administration
Master of Arts Research Report Submitted in partial fulfillment of the requirements for a Master of Arts degree February 2018
Keywords: International economic relations; South Africa--Foreign relations--China; China--Foreign relations--South Africa; South Africa--Social conditions